2023
DOI: 10.1126/science.adh2586
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence on the productivity effects of generative artificial intelligence

Abstract: We examined the productivity effects of a generative artificial intelligence (AI) technology, the assistive chatbot ChatGPT, in the context of midlevel professional writing tasks. In a preregistered online experiment, we assigned occupation-specific, incentivized writing tasks to 453 college-educated professionals and randomly exposed half of them to ChatGPT. Our results show that ChatGPT substantially raised productivity: The average time taken decreased by 40% and output quality rose by 18%. Inequality betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(69 citation statements)
references
References 32 publications
1
65
2
1
Order By: Relevance
“…Eloundou et al (2023) list accountants, auditors, and tax preparers as having 100% exposure to significant automation. Noy and Zhang (2023) demonstrate that ChatGPT leads to enhanced productivity, job satisfaction, and self-efficacy, with a notable advantage for low-ability workers. Although there are papers discussing ChatGPT's implementation in different disciplines such as education, healthcare, medicine, environment, and law (e.g., Aydın & Karaarslan, 2022;Choi et al, 2023;Frye, 2022;Mann, 2023), rare scholars have explored the promising applications of ChatGPT in the accounting field (De Kok, 2023;Gu et al, 2023;Noy & Zhang, 2023).…”
Section: Literature Reviewmentioning
confidence: 84%
See 2 more Smart Citations
“…Eloundou et al (2023) list accountants, auditors, and tax preparers as having 100% exposure to significant automation. Noy and Zhang (2023) demonstrate that ChatGPT leads to enhanced productivity, job satisfaction, and self-efficacy, with a notable advantage for low-ability workers. Although there are papers discussing ChatGPT's implementation in different disciplines such as education, healthcare, medicine, environment, and law (e.g., Aydın & Karaarslan, 2022;Choi et al, 2023;Frye, 2022;Mann, 2023), rare scholars have explored the promising applications of ChatGPT in the accounting field (De Kok, 2023;Gu et al, 2023;Noy & Zhang, 2023).…”
Section: Literature Reviewmentioning
confidence: 84%
“…Noy and Zhang (2023) demonstrate that ChatGPT leads to enhanced productivity, job satisfaction, and self-efficacy, with a notable advantage for low-ability workers. Although there are papers discussing ChatGPT's implementation in different disciplines such as education, healthcare, medicine, environment, and law (e.g., Aydın & Karaarslan, 2022;Choi et al, 2023;Frye, 2022;Mann, 2023), rare scholars have explored the promising applications of ChatGPT in the accounting field (De Kok, 2023;Gu et al, 2023;Noy & Zhang, 2023). In the rapidly evolving AI landscape, our study serves as one of the initial explorations of ChatGPT in accounting, echoing the calls made in accounting literature for more research dedicated to emerging technologies within the accounting domain (Fisher et al, 2016;Sutton et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 84%
See 1 more Smart Citation
“…In research, ChatGPT is renowned as an expert writing assistant. A recent experiment showed that college‐educated professionals using ChatGPT enjoyed substantially increased productivity in occupation‐specific, incentivized writing tasks 28 . Using ChatGPT to polish later drafts of academic writing for improved readability and language is recommended.…”
Section: Current Use and Limitations Of Chatgpt For Mental Health Pro...mentioning
confidence: 99%
“…Unlike traditional automation processes, which rely on explicitly programmed sequences, ML is designed to handle large datasets and high variability across both predictive and generative tasks. [1] The success of models such as ChatGPT in natural language processing (NLP) [2] and DALL-E in computer vision (CV) [3] has drawn public attention to the emerging field of AIGC. Beyond NLP and CV, AIGC is becoming a crucial scientific tool for addressing inverse design challenges, aimed at discovering new materials and structures with targeted functionalities.…”
Section: Introductionmentioning
confidence: 99%